A Mark-Up Model of Inflation for Morocco - Bennouna, Hicham (International Journal of Economics and Financial Issues, 2015)
We follow Brouwer and Ericsson (1998) approach in order to estimate a mark-up model of price over unit costs in Morocco from 1997q1 to 2013q2. This kind of models assumes that the equilibrium price level is set as a markup on some combination of input prices. Therefore, by estimating the short-run and long-run price elasticities with respect to unit labor costs and import prices, it’s possible to calculate the impact of supply shocks related to production costs. This treatment of price dynamics is at the heart of the modern approach to modelling inflation, both for forecasting and for policy analysis. The mark-up model identified in this paper highlight the fact that unit labor costs and import prices are key factors in the price setting strategy of the Moroccan firms. Keywords: mark-up; inflation; import prices; production costs; price setting. JEL Classifications: E50; E52; E58